Hubungan Gangguan Fungsi Kognitif dengan Tingkat Perilaku Merokok pada Mahasiswa Fakultas Sains dan Teknik Universitas Nusa Cendana - Miftahul Huda; Kartini Lidia; Sangguana Marthen Jacobus Koamesah; Iswaningsih Iswaningsih (Jurnal Inovasi Global, 2026)
Tobacco kills more than 8 million people a year. 19.2% of students in Indonesia and 38.3% of boys and 2.4% of girls are smokers. Tobacco or cigarette products contain at least 250 chemicals that are known to be toxic or cause cancer such as carbon monoxide, tar and nicotine. CO gas binds to Hb 250 times stronger than O2, thereby reducing oxygen transport to the brain. Chronic nicotine use has a significant effect on decreasing the availability of the dopamine transporter, causing impairment and decreased cognitive function. Based on prevalence data, it was found that cognitive impairment in Engineering students was quite high, namely 48.2%. This study aims to analyze the relationship between cognitive dysfunction and the level of smoking behavior in students of the Faculty of Science and Engineering, University of Nusa Cendana. This study used an observational research design analytics with case controll design. Samples were taken using the non-probability sampling consecituve technique with a total sample of 130 people. Data collection using the Montreal Cognitive Assessment Indonesian version (MoCA-Ina) and smoking behavior questionnaire. The data analysis used is the Chi-Square test. There is a significant relationship between cognitive dysfunction and the level of smoking behavior in the case and control groups with a p value = 0.000 and an Odds Ratio (OR) = 4.18. Impaired cognitive function can be caused by smoking behavior.